The influence of the banking sector on central bank independence and inflation control : the of Lebanon between 1985 and 1991 - Nasser, Yassar (Cranfield University, 2008)
A substantial amount of prior research has focused on the relation between Central Bank Independence (CBI) and inflation control. However, this research is mainly theoretical or conducted using cross-country statistical regressions and correlations in the developed world. Little attention has been given to understanding this relation in emerging nations or the influence of interest groups on CBI and inflation in a specific context. This thesis addresses both gaps by conducting an in-depth observation and analysis of this relation in a single country (Lebanon) and the influence of the banking sector on both CBI and inflation during a period of high inflation. This empirical evidence in the case of Lebanon shows that Central Bank Independence from the government – even though abundant and complete – was not enough to control inflation. The influence of the banking sector on both CBI and inflation was more important. This work makes a contribution to knowledge through highlighting the importance of national contexts when evaluating the CBI-inflation relation. Furthermore, this research extends our understanding of the literature and its gaps, and presents a new way to conduct in-depth studies in the field. Finally, it provides practical insights that are of importance to central bankers, especially in emerging nations.
Keywords: Central Bank Independence; inflation; Lebanon; interest groups; Financial Sector; Opposition to inflation (FOI); Political Economy; Banks